2004
DOI: 10.3844/ajassp.2004.193.201
|View full text |Cite
|
Sign up to set email alerts
|

House Price Prediction: Hedonic Price Model vs. Artificial Neural Network

Abstract: The objective of this paper is to empirically compare the predictive power of the hedonic model with an artificial neural network model on house price prediction. A sample of 200 houses in Christchurch, New Zealand is randomly selected from the Harcourt website. Factors including house size, house age, house type, number of bedrooms, number of bathrooms, number of garages, amenities around the house and geographical location are considered. Empirical results support the potential of artificial neural network o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(172 citation statements)
references
References 31 publications
11
154
0
7
Order By: Relevance
“…In the direct real estate literature, the performance of neural networks is less conclusive. The quality of the house price predictions obtained with this technique is supported by some researchers (Nguyen and Cripps 2001;Limsombunchai et al 2004;Peterson and Flanagan 2008), but criticized by others (Worzala et al 1995;Lenk et al 1997).…”
Section: Literature Reviewmentioning
confidence: 91%
“…In the direct real estate literature, the performance of neural networks is less conclusive. The quality of the house price predictions obtained with this technique is supported by some researchers (Nguyen and Cripps 2001;Limsombunchai et al 2004;Peterson and Flanagan 2008), but criticized by others (Worzala et al 1995;Lenk et al 1997).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Pudaruth's research also concluded that limited number of instances in data set do not offer high prediction accuracies [1]. Limsombunchai [4] concluded in his research that neural networks are better in estimating price of a house. His method offered higher prediction accuracy as compared to hedonic method.…”
Section: Related Workmentioning
confidence: 99%
“…The limitation of this research was that it offered strong evidence of prediction superiority but did not talk of forecasting capability between the two methods used. Also, actual house prices are missing in the research and only estimated prices were used avoiding difficulties of data collection [4].…”
Section: Related Workmentioning
confidence: 99%
“…In his research Rahadi, et al [14] divide these factors into three main groups, there are physical condition, concept and location. Physical conditions are properties possessed by a house that www.ijacsa.thesai.org can be observed by human senses, including the size of the house, the number of bedrooms, the availability of kitchen and garage, the availability of the garden, the area of land and buildings, and the age of the house [15], while the concept is an idea offered by developers who can attract potential buyers, for example, the concept of a minimalist home, healthy and green environment, and elite environment.…”
Section: A House Price Affecting Factorsmentioning
confidence: 99%